Analisis Perlindungan Terhadap Anak di Indonesia - Abi Hasan (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2017)
Law No. 23 of 2002 on Child Protection has been clearly defined about the protection of children to the rules of criminal sanctions for those who violate the rights of the child. The law also explains that the implementation of child protection is parents, family, government and state. Under Article 1, paragraph 2, the Child Protection Act provides that child protection is all activities to guarantee and protect children and their rights in order to live, grow, develop and participate optimally in accordance with human dignity and protection, Violence and discrimination. Therefore, protection efforts should be made to realize the welfare of children by providing guarantees for the fulfillment of their rights without any discriminatory treatment.